Environmental, Health, and Legislation Considerations for Rational Design of Nonreactive Flame‐Retardant Additives for Polymeric Materials: Future Perspectives. Issue 24 (14th July 2022) - Reynolds, Karina J.; Zagho, Moustafa M.; Robertson, Mark; Qiang, Zhe; Nazarenko, Sergei
Abstract: Increasing polymer usage has demanded functional additives that decrease fire hazards for end users. While traditional flame‐retardant (FR) additives, such as halogenated, phosphorus, and metal hydroxides, greatly reduce flammability and associated fire hazards, research has continually exposed a litany of health and environmental safety concerns. This perspective aims to identify the key components of a successful FR additive and address material, environmental, and health concerns of existing additives. Legislation surrounding FRs and persistent organic pollutants is also discussed to highlight political perception that has resulted in the increased chemical regulations and subsequent banning of FR additives. Finally, future directions of this field regarding nonreactive additives, focusing on the use of bioinspired materials and transition metal chemistries to produce alternatives for polymers with efficacies surpassing traditional additives are presented. Abstract : The article provides an overview of currently used nonreactive flame‐retardant additives and identifies their material, environmental, and health concerns. This article also draws attention to legislation surrounding flame‐retardant additives and discusses the implications of overgeneralized chemical bans. Finally, the future of environmentally more benign nonreactive flame‐retardant additives is highlighted, focusing on the use of biopolymers and transition metal chemistries.